2017
DOI: 10.1186/s12889-017-4222-y
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of intimate partner violence and its association with symptoms of depression; a cross-sectional study based on a female population sample in Sweden

Abstract: BackgroundIntimate Partner Violence (IPV) is the most common type of violence targeting women. IPV includes acts of physical aggression, sexual coercion, psychological abuse and controlling behaviors and these forms of violence often coexist in the same relationship. Living with IPV is associated with serious mental health outcomes such as depression and depressive symptoms. Few population based studies from Sweden have investigated the relationship between different forms of IPV and women’s depressive symptom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
44
1
7

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(70 citation statements)
references
References 54 publications
11
44
1
7
Order By: Relevance
“…Second, the sample was composed almost exclusively by women reporting gender violence or gender violence reported by a third party (cases of severe violence), but excluded women who had not reported their aggressor as a result of the psychological injury itself or for other reasons (Boira, Carbajosa, & Méndez, 2016). Third, the victims of the present study were simultaneously victims of physical and psychological violence as confirmed by the legal judgements (besides being victims of economic or sexual violence, regardless as to whether it was cited or not in the legal judgement), and both are the most common manifestations of gender violence (Lövestad, Löve, Vaez, & Krantz, 2017;Novo, Herbón, & Amado, 2016), that is, mixed violence leading to greater injury to health (Fernández-González, Calvete, & Orue, 2017;Hegarty et al, 2012), whilst in other manifestations of violence injury may have less of an impact (Moral, García, Cuetos, & Sirvent, 2017). Fourth, the measures of injury to health overlapped with the most relevant dimensions of mental health and the most frequent clinical diagnoses (the SCL-90-R was designed on the basis of the DSM), without evaluating directly disorders related to secondary traces of psychological violence such as impulsive or sexual disorders, and those related to drug abuse (Dillon, Hussain, Loxton, & Rahman, 2012;Fariña et al, 2014).…”
Section: Discussionmentioning
confidence: 88%
“…Second, the sample was composed almost exclusively by women reporting gender violence or gender violence reported by a third party (cases of severe violence), but excluded women who had not reported their aggressor as a result of the psychological injury itself or for other reasons (Boira, Carbajosa, & Méndez, 2016). Third, the victims of the present study were simultaneously victims of physical and psychological violence as confirmed by the legal judgements (besides being victims of economic or sexual violence, regardless as to whether it was cited or not in the legal judgement), and both are the most common manifestations of gender violence (Lövestad, Löve, Vaez, & Krantz, 2017;Novo, Herbón, & Amado, 2016), that is, mixed violence leading to greater injury to health (Fernández-González, Calvete, & Orue, 2017;Hegarty et al, 2012), whilst in other manifestations of violence injury may have less of an impact (Moral, García, Cuetos, & Sirvent, 2017). Fourth, the measures of injury to health overlapped with the most relevant dimensions of mental health and the most frequent clinical diagnoses (the SCL-90-R was designed on the basis of the DSM), without evaluating directly disorders related to secondary traces of psychological violence such as impulsive or sexual disorders, and those related to drug abuse (Dillon, Hussain, Loxton, & Rahman, 2012;Fariña et al, 2014).…”
Section: Discussionmentioning
confidence: 88%
“…Consequently, research has been dedicated to understanding this gender asymmetry, focusing largely on the historically and socially constructed influence of patriarchy in allowing men to control and dominate their female partners (Fisher, 2013;Sugarman & Frankel, 1996;Walsh, Spangaro, & Soldatic, 2015). Indeed, statistics gathered from clinical samples (e.g., men in prisons, women in shelters) indicate that most victims of IPV are women (Johnson 1995(Johnson , 2006Lövestad, Löve, Vaez, & Krantz, 2017).…”
Section: Attitudes and Behavioural Intentions Associated With Intimatmentioning
confidence: 99%
“…In this context, research points to the difficulties in attending to victims of violence, mainly sexual, especially regarding the collection of information for completing the notification form and unprepared professionals. 20 With Law 12,845 / 2013, it is compulsory and integral to provide assistance to victims of sexual violence, with immediate and multiprofessional care, including diagnosis and treatment of lesions, DNA collection, HIV testing, prophylaxis for pregnancy and sexually transmitted diseases. 19 The majority of male aggressors refer to male domination and cannot forget that, in Western societies, the conception of gender is linked to rules that shaped the social status that the subject occupies in the productive and reproductive system 21 .…”
mentioning
confidence: 99%
“…The absence or incomplete completion of the notification forms, especially in the emergency services, may be a consequence of the overload of professionals, and not everyone is aware of the importance of notification as a management tool in helping to create public policies, important knowledge so that the notification form is not regarded as an unnecessary obligation. 20 On the other hand, the large number of ignored data may be related to non-disclosure by the victim. Nurses report that women are afraid to report situations of domestic violence and that the creation of a bond, based on trust, becomes important in this type of care.…”
mentioning
confidence: 99%